Murine Adherent and Invasive E. coli Induces Chronic Inflammation and Immune Responses in the Small and Large Intestines of Monoassociated IL-10-/- Mice Independent of Long Polar Fimbriae Adhesin A. Issue 5 (21st December 2018) - Schmitz, Julia M; Tonkonogy, Susan L; Dogan, Belgin; Leblond, Anna; Whitehead, Kristi J; Kim, Sandra C; Simpson, Kenneth W; Sartor, R Balfour
Abstract: Background: Adherent and invasive Escherichia coli (AIEC) is preferentially associated with ileal Crohn's disease (CD). The role of AIEC in the development of inflammation and its regional tropism is unresolved. The presence of long polar fimbriae (LPF) in 71% of ileal CD AIEC suggests a role for LPF in the tropism and virulence of AIEC. The aim of our study is to determine if AIEC, with or without LpfA, induces intestinal inflammation in monoassociated IL-10 -/- mice. Methods: We compared murine AIEC strains NC101 (phylogroup B2, LpfA-) and CUMT8 (phylogroup B1, LpfA+), and isogenic mutant CUMT8 lacking lpfA 154, with a non-AIEC ( E. coli K12), evaluating histologic inflammation, bacterial colonization, mucosal adherence and invasion, and immune activation. Results: IL-10 -/- mice monoassociated with AIEC (either CUMT8, CUMT8:Δ lpfA, or NC101) but not K12 developed diffuse small intestinal and colonic inflammation. There was no difference in the magnitude and distribution of inflammation in mice colonized with CUMT8:Δ lpfA compared with wild-type CUMT8. Bacterial colonization was similar for all E. coli strains. Fluorescence in situ hybridization revealed mucosal adherence and tissue invasion by AIEC but not K12. Production of the cytokines IL-12/23 p40 by the intestinal tissue and IFN-γ and IL-17 by CD4 T cells correlated with inflammation. Conclusions: IL-10 -/- mice monoassociated with murine AIEC irrespective of LpfA expression developed chronic inflammation accompanied by IL-12/23 p40 production in the small and large intestines and IFN-γ/IL-17 production by CD4 T cells that model the interplay between enteric pathosymbionts, host susceptibility, and enhanced immune responses in people with IBD.